ANALYSIS OF VOLCANIC STRUCTURE BASED ON RESISTIVITY DISTRIBUTION USING MAGNETOTELLURIC (MT) - UMUL KHAIR (NIM : 10213001), HIDAYATI
Indonesia, which has a population of more than 250 million people, certainly needs a huge supply of electrical energy. It also makes Indonesia one of the countries with a large number of renewable energy users and producers in Southeast Asia region. Electrical energy can be generated from several renewable energy sources such as water, wind, ocean waves, geothermal, and solar radiation. Geothermal is one of the renewable energy sources that have been widely used in Indonesia. To know the existence of geothermal source, a method of geophysics is needed. Geophysical method is a method that can be used to determine the subsurface structure of the earth based on physical parameters. One of the geophysical methods commonly used in geothermal exploration is the magnetotellurics method. In this research, modeling on magnetotellurics data on Kusatsu volcano area have been done. The Kusatsu-Shirane volcano is an active volcano located along the "volcanic front" (Sugimura, 1960) on Honshu Island, Japan. Volcanic activity of this mountain has been recorded since the year of 1805. The eruption created many crater holes around the summit of Mount Kusatsu-Shirane. The most recent phreatic eruption occurred in 1982-1983 in Yugama and Karegama craters. Most types of rock that made up Kusatsu-Shirane are andesite piroxen rock, the most common type of stone in Japan, and piroxen dacite. Magnetotelluric 1D modeling is carried out to obtain a volcanic subsurface model characterized by high-contrast resistivity.